71.6k views
1 vote
Solve x and y simultaneously if:


y + 7 = 2x

{x}^(2) - xy + {3y}^(2) = 15


1 Answer

3 votes

Answer:

make Y the subject in eqn........ 1

y + 7 = 2x

y = 2x - 7...........eqn 3

put y = 2x - 7 into eqn 2

x² - xy + 3y² = 15

x² - x(2x - 7) + 3(2x - 7)(2x - 7) = 15

x² - 2x² + 7x + 3(4x² + 14x -14x + 21) = 15

x² - 2x² + 7x + 12x² + 42x - 42x + 63 = 15

x² - 2x² + 7x + 12x² + 63 = 15

x² - 2x² + 12x² + 7x + 63 = 15

11x² + 7x + 63 - 15 = 0

11x² + 7x + 48 = 0

11x² + 7x = - 48

11x²/11 + 7x/11 = - 48/11

x² + 7x

User James South
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.